HUBUNGAN BEBAN KERJA PERAWAT DENGAN KEJADIAN LOW BACK PAIN (LBP) PADA PERAWAT PELAKSANA DI RS TK. III R.W MONGINSIDI MANADO - Sumangando, Monalisa; Rottie, Julia; Lolong, Jill (Universitas Sam Ratulangi, 2017)
Abstarct : The role of nurses in the hospital is very important, in which nurses have role to perfom nursing care. The tasks of a nurse are quite many. Due to many tasks that has to be done by nurses, their workloads will be affected. Excess of workloads would bring health-related impacts toars nurses, on of them is low back pain. Low Back Pain (LBP) is an unspecified condition that refer to acute or chronic pain symptom and discomfort feeling in or around lumbosacral region that can be caused by inflammation, degenerative process, malignancy, gynecologic disorder, trauma and metabolic dysfunction. The Aim of this research is to identify the association between nurses workload with the incident of low back pain on nurses. Sample of this research are 40 respondents which obtained with purposive sampling technique. This research used Observational analytic design with cross-sectional approach and the data was collected through observation and questioner. The result of this research based on Chi-square test is p-value = 0,365 > 0,05. It indicates no relationship between the workloas of nurse and the incidence of low back pain on nurses in RS. TK. III R. W. Monginsidi Manado. The recommendation for next research is to study about other factors that is possible to trigger LBP on nurses. Keyword: Nurses, Workload, low back pain. Abstrak : Peran perawat di ruamah sakit sangatlah penting karena perawat sebagai pemberi asuhan keperawatan. Tugas yang dilakukan perawat sangatlah banyak. Dengan banykanya tanggung jawab yang dilakukan perawat akan berdampak pada beban kerja perawat. Beban kerja yang berlebih akan berdampak pada kesehatan perawat salah satunya LBP. LBP adalah suatu kondisi tidak spesifik yang mengacu pada keluhan nyeri akut atau kronik dan ketidaknyamanan pada atau di dekat daerah lumbosakral, yang dapat disebabkan oleh inflamasi, proses degeneratif, keganasan, kelainan ginekologi, trauma, dan gangguan metabolik. Tujuan penelitian ini untuk mengetahui hubungan beban kerja perawat dengan kejadi low back pain pada perawat pelaksana. Sampel brjumlah 40 responen yang didapat dengan menggunakan teknik purposive sampling. Desain penelitian observasional analitik dengan pendekatan Cross Sectional dan data dikumpulkan dari responden dengan menggunakan lembar kuesioner dan observasi. Kesimpulan uji Chi Square diperoleh nilai signifikan p = 0,365 > 0,05. Hal ini menunjukan bahwa tidak ada hubungan antara beban kerja perawat dengan kejadi low back pain pada perawat pelasana di RS. TK. III R.W Monginsidi Manado. Kata Kunci : Perawat, Beban Kerja, Low Back Pain